In silico assessment of collateral eddy current heating in biocompatible implants subjected to magnetic hyperthermia treatments. (1st January 2021) - Rubia-Rodríguez, Irene; Zilberti, Luca; Arduino, Alessandro; Bottauscio, Oriano; Chiampi, Mario; Ortega, Daniel
Abstract: Purpose: Bearing partially or fully metallic passive implants represents an exclusion criterion for patients undergoing a magnetic hyperthermia procedure, but there are no specific studies backing this restrictive decision. This work assesses how the secondary magnetic field generated at the surface of two common types of prostheses affects the safety and efficiency of magnetic hyperthermia treatments of localized tumors. The paper also proposes the combination of a multi-criteria decision analysis and a graphical representation of calculated data as an initial screening during the preclinical risk assessment for each patient. Materials and methods: Heating of a hip joint and a dental implant during the treatment of prostate, colorectal and head and neck tumors have been assessed considering different external field conditions and exposure times. The Maxwell equations including the secondary field produced by metallic prostheses have been solved numerically in a discretized computable human model. The heat exchange problem has been solved through a modified version of the Pennes' bioheat equation assuming a temperature dependency of blood perfusion and metabolic heat, i.e. thermorregulation. The degree of risk has been assessed using a risk index with parameters coming from custom graphs plotting the specific absorption rate (SAR) vs temperature increase, and coefficients derived from a multi-criteria decision analysis performed following the MACBETH approach. Results: The comparison of two common biomaterials for passive implants - Ti6Al4V and CoCrMo - shows that both specific absorption rate (SAR) and local temperature increase are found to be higher for the hip prosthesis made by Ti6Al4V despite its lower electrical and thermal conductivity. By tracking the time evolution of temperature upon field application, it has been established that there is a 30 s delay between the time point for which the thermal equilibrium is reached at prostheses and tissues. Likewise, damage may appear in those tissues adjacent to the prostheses at initial stages of treatment, since recommended thermal thresholds are soon surpassed for higher field intensities. However, it has also been found that under some operational conditions the typical safety rule of staying below or attain a maximum temperature increase or SAR value is met. Conclusion: The current exclusion criterion for implant-bearing patients in magnetic hyperthermia should be revised, since it may be too restrictive for a range of the typical field conditions used. Systematic in silico treatment planning using the proposed methodology after a well-focused diagnostic procedure can aid the clinical staff to find the appropriate limits for a safe treatment window. Graphical Abstract: UF0001